MANAJEMEN STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH ALIYAH DARUL FALAH BANDAR LAMPUNG - fahri, agung (STIT Bustanul 'Ulum Lampung Tengah, 2025)
This study explores the strategic management practices of the principal of Madrasah Aliyah Darul Falah Bandar Lampung in enhancing teacher performance. In the context of increasing educational demands, school leadership plays a pivotal role in improving teaching quality through planned, measurable strategies. The research aims to identify the principal’s strategic steps, evaluate their effectiveness, and understand their impact on teachers' pedagogical competence, discipline, and digital literacy. Using a qualitative approach with descriptive methods, data were collected through observation, interviews, and documentation. The principal’s strategy was implemented through four key stages: SWOT-based internal-external analysis, strategic vision formulation, program implementation (training, supervision, teacher collaboration), and continuous evaluation with feedback integration. The findings indicate significant improvement in teacher performance, particularly in lesson preparation, attendance, and technology integration. These outcomes suggest that strategic planning based on participatory analysis and reflective evaluation can create a collaborative, adaptive, and forward-looking school culture. The study concludes that the role of a visionary and responsive principal is crucial in shaping a high-performing educational institution. These findings provide a practical model that can be adopted by other Islamic schools to improve teacher performance. Future studies could explore the quantitative impact of such strategies on student outcomes or replicate the model across different educational levels.